THE BEST TEACHER - Zarnigora, Rasulova Raxmatjon qizi (Educational Research in Universal Sciences, 2023)
This article is written to show a bright way to teachers for becoming lovely teacher in classroom and this article helps instructors to manage their lessons effectively.